Investigating the functional properties of the multi-allelic copy number variable DEFA1A3 locus and their effects on gene expression and disease - AlHamidi, Reem (2023)
Background Human α-defensins have important roles in innate immunity and exhibit antimicrobial properties against pathogens. The copy variable locus of human α-defensin genes - denoted as DEFA1A3 - is a multi-allelic copy number variable (CNV) region located on chr8p23.1. The DEFA1A3 CNV genes cluster in a single tandem repeat array, consisting of a 19 kb full repeat (either DEFA1 or DEFA3) in tandem and a 10 kb partial repeat (either DEFA1 or DEFA3) at the centromeric end of the array. Individuals exhibit 3 to 16 DEFA1A3 diploid gene copies in a European (EUR) population. Associations of nearby SNPs with IgA Nephropathy (IgAN) and Periodontitis (PD) have been demonstrated by GWAS (genome wide association studies). It was reported that low DEFA1A3 copy number increases the risk of IgAN but no such conclusion was made for periodontitis. It is expected that gene copy number should correlate with levels of transcripts. However, previous studies of DEFA1A3 copy number association to RNA levels have been inconclusive, with studies conducted so far having small sample sizes. Long-read sequencing has made it possible to sequence regions uninterruptedly but inferring true haplotype structures is challenging especially with repeated structures. Aims In this work, three study approaches were established to study the functional properties of the multi-allelic variants and their functional effects on diseases in the DEFA1A3 CNV locus. These study approaches include 1) examining the association of total DEFA1A3 copy number with Aggressive Periodontitis (AgP) in a European-based population, 2) replicating the association study of total DEFA1A3 copy number with RNA levels and DEFA1:DEFA3 genomic ratio to transcript ratio with a larger sampler size, and 3) evaluating Oxford Nanopore Technologies (ONT) sequencing platform to reconstruct the diploid DEFA1A3 CNV locus using targeted sequencing approaches from samples such as NA12878. Results In the case-control association analysis from 700 European controls and 454 (AgP) cases, we found evidence of an association of AgP and local (telomeric) SNPs but not with DEFA1A3 copy number. In a study of genomic and RNAseq data from a UK-based population of 197 samples, no evidence of association was detected between total DEFA1A3 copy number and transcript levels in three human immune cells. By contrast, there was evidence of clear correlation between relative ratios of DEFA1:DEFA3 RNA levels and equivalent gene numbers. In the nanopore sequencing approach, CRISPR-cas9 enrichment and long amplicon sequencing (tiling path) were used. We were able to successfully reconstruct the DEFA1A3 haplotypic structures for some samples such as NA12878, NA12760, and NA12248 but not others. The CRISPR-cas9 method appears to be the most suitable approach in sequencing repeated complex structures as it requires reduced repeat sorting and less repeat reconstruction.